Jesus, the Only Way to God Must You Hear the Gospel to be Saved?. - Piper, John. (Grand Rapids : Baker Publishing Group, 2010)
Bestselling author offers a timely plea for the evangelical church to consider what is at stake in surrendering the unique, universal place of Jesus in salvation.
7. Is Conscious Faith In Jesus Necessary For Salvation? Part Four: The Missionary Task As Seen By Paul And Johnconclusion; A Note On Resources: Desiring God.
Description based upon print version of record.
Keywords: Jesus Christ -- Person and offices; Jesus Christ; Salvation -- Christianity; Electronic books